Since you’re multiplying n^-6 and n^3, you can add the exponents: -6+3 = -3
n^-6 * n^3 = n^-3
If you need to finish without having a negative exponent in your answer, then remember a negative exponent means that factor is on the wrong side of the fraction.
n^-3 = n^-3 / 1 = 1/n^3
when the factor moves to the other side of the fraction, the side of the exponent changes.
Answer:
37°
Step-by-step explanation:
Sum of angles in a triangle = 180°
So 96 + 47 = 143
180 - 143 = 37
Answer:
x/12
Step-by-step explanation:
1/4 of a pan of brownies leftover.
=1/4 of x
=1/4*x
=x/4
If Carter and two of his friends shares the leftover=3 people
Each friend will get
x/4÷3
=x/4×1/3
=x/12
The value is 4 because 4b is also 4 times three which is twelve then you divide 12 by three and get 4
Answer:
1 and -1
Step-by-step explanation:
The absolute value means that the answer will always come out as positive, meaning that both 1 and -1 fit in this equation.